Improving The Eleventh Grade Students’ Reading Comprehension Achievement by using Folklore at MAN 2 Palembang - Yolanda Gadis Baroqqah; Nike Angraini (Universitas Indo Global Mandiri, 2020)
ABSTRACTThe objectives of the study were to find out (1) whether there was significant improvement of students’ reading comprehension achievement after being taught by using folklore (2) to find out whether there was significant mean difference of reading comprehension achievement between the students who were taught by using folklore and those who were not. The method of the study was quasi-experimental design, non-equivalent control design. The population was all the eleventh grade students’ at MAN 2 Palembang. Sixty-eight students were purposively selected and equally divided into experimental and control groups. The data were analyzed by using t-test (Paired Samples t-test and Independent Samples t-test). The findings revealed that by using folklore significantly improved the students’ reading comprehension achievement (t=17.158). The mean score of post-test in experimental group was75.06, meanwhile the mean score of post-test in control group was 59.59. The result in experimental group was better than control group. It means the use of folklore improved students’ reading comprehension achievement.Keyword : improving, folklore, reading comprehension achievementABSTRAKTujuan dari penelitian ini adalah untuk mengetahui (1) apakah ada peningkatan yang signifikan dari prestasi membaca siswa setelah diajarkan dengan menggunakan cerita rakyat (2) untuk mengetahui apakah ada perbedaan rata-rata yang signifikan dari prestasi membaca antara siswa yang diajarkan dengan menggunakan cerita rakyat dan mereka yang tidak diajarkan. Metode penelitian menggunakan desain quasi-experimental, non-equivalent control design. Populasi didalam penelitian aadalah semua siswa kelas XI (Sebelas) di MAN 2 Palembang. Enam puluh delapan siswa dipilih secara purposif untuk menjadi sampel dalam penelitian ini dan dibagi rata ke dalam kelompok eksperimen dan kontrol. Data yang didapat dianalisa dengan menggunakan uji-t (Paired Samples t-test and Independent Samples t-test). Hasil dari penelitian mengungkapkan bahwa dengan menggunakan cerita rakyat dapat meningkatkan prestasi membaca siswa secara signifikan (t = 17, 158). Nilai rata-rata posttest pada kelompok eksperimen adalah 75,06, sedangkan nilai rata-rata pada kelompok kontrol adalah 59,59. Hasil pada kelompok eksperimen lebih baik daripada kelompok kontrol. Ini berarti penggunaan cerita rakyat meningkatkan prestasi membaca siswa.Kata kunci : Peningkatan, cerita rakyat, prestasi membaca pemahaman